Legal Fiction of Corporate Zakat: Ontological Paradox and Functional Hypocrisy in Islamic Financial Reporting - rhonny riansyah; Iskandar Arnel; Alchudri Alchudri; Novi Yanti; Sofiandi Sofiandi (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2026)
This study aims to examine the ontological paradox and systemic inconsistency of the corporate status as a legal subject of zakat (muzakkī) in contemporary Islamic jurisprudence. Adopting a critical interpretive paradigm and abductive design, this study synthesizes Foucauldian genealogy, John Searle's "Institutional Facts," Gunther Teubner's "Legal Hypocrisy," and the epistemic decomposition of the AAOIFI FAS 39 zakat-based accounting equation to deconstruct the corporate status. It is revealed that the recognition of the corporate status as muzakkī is an incoherent legal fiction. Genealogically, a corporation is an institutional fact that lacks the spiritual instruments of taklīf prerequisites, namely ʿaql (reason) and niyyah (intention). The epistemic decomposition of the zakat-based accounting equation proves the occurrence of an ontological paradox. Formally, a corporation is recognized as muzakkī, but operationally it is treated only as an agent (wakīl) of shareholders. This incoherent legal fiction is identified as "legal hypocrisy," intended to maintain religious legitimacy amidst economic pragmatism. Classical Islamic jurisprudence is substantively far more "honest" and anticipatory than modern legal theory in responding to the corporate phenomenon. This study recommends ontological reconstruction to end this functional hypocrisy by returning the position of zakat to the human subject (natural person) and affirming the pure position of corporations as wakīl (agent), without any pretensions to being legal subjects with independent taklīf obligations.